EFFECTIVE SELF-RELIANCE TEACHING MODEL USING VISUAL STORYTELLING FOR ELEMENTARY STUDENTS IN INDONESIA - Mujahidin, Endin; Ruhenda, Ruhenda; Nasution, Syamsuddin Ali (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2018)
The aim of this study was to design the visual storytelling teaching model addressed to self-reliance and implement it for increasing self-reliance of elementary students. This self-reliance study was focused on three main parameters which were self-command in daily activities, self-confidence and self-decision. This study was performed by survey, teaching materials designing and teaching delivery method implementation. The developed teaching materials were serial stories in animated pictures. Self-reliance was classified in three categories which were very good, good and enough. The result showed that average score of self-reliance of 1,805 students (from 6 schools) for three parameters above was in enough categories. After coaching by storytelling teaching model that involved 287 students and 12 teachers, the score of self-reliance were come up into good categories. The score increased 1.00 and 0.79 point for younger and older class respectively. This visual storytelling strategy was effective for self-reliance development in Indonesia and teachers should be involved intensively more than delivering only. Materials developed in this study are recommended to be applied as co-curricular activities or introduce in regular curriculum.The beneficial of this study is information on the importance of interesting teaching method and role of teacher in building self-reliance.